1993
DOI: 10.1177/002221949302600602
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Strategy Instruction: A Potential Model for Teaching Content Area Subjects to Adolescents with Learning Disabilities

Abstract: In part because learning strategies are often taught in isolated resource settings outside of the contexts in which students with learning disabilities are expected to apply this knowledge, generalization has been a significant challenge to educators. To address this problem, an instructional model is proposed for integrating cognitive strategy instruction and content area instruction when teaching students in content area classes. Teacher-directed instructional procedures, cooperative learning, and direct exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 41 publications
3
40
0
1
Order By: Relevance
“…Many intervention programs have been made to teach students to plan, implement, and evaluate strategic approaches to learning reading and problem solving (e.g., Montague, 1992;Paris & aka, 1989;Vauras, Lehtinen, Kinnunen, & Salonen, 1992). According to Ellis (1993), the interactive strategy instruction model provides teachers with a set of instructional routines and devices that enhance students' understanding and remembering of subject matter in a given content area, as well as improving their performance on academic tasks. The aim is to teach explicitly the use of powerful information skills, such as metacognition, strategies, and self-motivation strategies.…”
Section: Aimingfor Expert-like Strategiesmentioning
confidence: 99%
“…Many intervention programs have been made to teach students to plan, implement, and evaluate strategic approaches to learning reading and problem solving (e.g., Montague, 1992;Paris & aka, 1989;Vauras, Lehtinen, Kinnunen, & Salonen, 1992). According to Ellis (1993), the interactive strategy instruction model provides teachers with a set of instructional routines and devices that enhance students' understanding and remembering of subject matter in a given content area, as well as improving their performance on academic tasks. The aim is to teach explicitly the use of powerful information skills, such as metacognition, strategies, and self-motivation strategies.…”
Section: Aimingfor Expert-like Strategiesmentioning
confidence: 99%
“…Much evidence indicates that students with disabilities lack these skills, which are critical for learning, solving problems, and completing tasks independently in general education classrooms. These skills may be taught in a separate setting by a teacher of students with disabilities or, as Ellis (1993) has proposed, as part of an Integrated Strategy Model that combines classroom content and general strategy in-3 struction. In the latter model, the general and special education teachers teach these skills collaboratively.…”
Section: Secondary Curricular Content Needs For Students With Mild DImentioning
confidence: 99%
“…4. Learning strategies programs (Deshler, Schumaker, Lenz, & Ellis, 1984;Ellis, 1993). This approach is not designed to teach specific content but, rather, focuses on teaching students skills related to "how to learn."…”
mentioning
confidence: 99%
“…Specifically, in most approaches, a set of strategies used by proficient learners is outlined and then conveyed to less proficient learners, most often by direct instruction (e.g., Borkowski & Muthukrishna, 1992;Ellis, 1993;Pressley et al, 1987;Schumaker & Deshler, 1984). Research has shown that students' task performance generally improves following strategy instruction.…”
Section: Problems With Current Instructional Modelsmentioning
confidence: 99%